River of shadows Eadweard Muybridge and the technological wild west - Solnit, Rebecca 1961- (Viking, 2003)
A survey of the historical contributions of Eadweard Muybridge documents his role in filmmaking technology and as a war photographer before standing trial for the murder of his wife's lover.
Keywords: Muybridge, Eadweard <1830-1904>; Muybridge, Eadweard -- 1830-1904; Geschichte; Chronophotography -- History; Cinematographers -- United States -- Biography; Photographers -- United States -- Biography; Fotografie; Technologie; USA; USA -- Weststaaten; Biografie